Volatility Spillover in the Indian Commodity Market : A Comparative Assessment of Various Commodity Segments - Sonia,; Narwal, Karam Pal (Indian Journal of Finance, 2023)
Purpose : The present study concentrated on analyzing the volatility spillover effect between spot and futures returns of eight commodities traded on India’s multi-commodity exchange (MCX). This study intended to compare the volatility spillover effect within spot and futures returns of four commodity segments, such as metal, energy, bullion, and agriculture, to determine whether the volatility spillover effect was similar in all categories or not. Methodology : The sample of the study included two commodities from each category. The closing spot and futures prices were extracted from MCX India Ltd.’s authenticated sources for the period spanning from January 2009 – March 2020 for all sampled commodities except cotton (for cotton, September 2011 – March 2020). The present study used the EGARCH model to study the volatility transmission between markets. Findings : The outcomes of the study indicated that there existed a volatility spillover effect in all sampled commodities. Also, the outcomes revealed that the volatility spillover effect in all segments was quite different from each other. Practical Implications : A comparative assessment of the volatility spillover mechanism existing between the two markets of various groups of commodities will be advantageous for investors, traders, and portfolio managers in selecting the most profitable group of commodities for investment, trading, and portfolio optimization. Originality/Value : In India, there have been very few empirical studies that compare the comparative aspects of spillover effects across various commodity segments.